Adult female acne: a guide to clinical practice - Edileia Bagatin; Thais Helena Proença de Freitas; Maria Cecilia Rivitti-Machado; Beatriz Medeiros Ribeiro; Samanta Nunes; Marco Alexandre Dias da Rocha (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Background: Acne in women is often associated with anxiety and depression, and may persist from adolescence as well as manifest for the first time in adulthood. Genetic and hormonal factors contribute to its etiopathogenesis, and maintenance treatment is required, usually for years, due to its clinical evolution. Objective: To develop a guide for the clinical practice of adult female acne. Methods: A team of five experts with extensive experience in acne conducted a literature review of the main scientific evidence and met to discuss the best practices and personal experiences to develop a guide containing recommendations for the clinical practice of adult female acne. Results: The group of specialists reached consensus on the main guidelines for clinical practice, providing detailed recommendations on clinical picture, etiopathogenesis, laboratory investigation and treatment of adult female acne. Conclusion: Different from teenage acne, adult female acne presents some characteristics and multiple etiopathogenic factors that make its management more complex. This guide provides recommendations for best clinical practices and therapeutic decisions. However, the authors consider that additional studies are needed in order to provide more evidence for adult female acne to be better understood.